KOMISI YUDISIAL DAN PENGAWASAN HAKIM: MENUJU PERADILAN YANG PROFESIONAL DAN BERINTEGRITAS - Alfian Dj DJafar (Perkumpulan Maju Karya Yogyakarta, 2025)
The Judicial Commission (KY) plays a crucial role in maintaining the honor and conduct of judges in Indonesia, established in response to the weak internal oversight of the Supreme Court (MA). However, the effectiveness of the KY is hampered by limited authority and an inability to firmly address violations. Data reveals that 29 judges were involved in corruption cases between 2011-2024, with bribery values reaching Rp 107.9 billion, reflecting a failure of internal oversight. Efforts to weaken the KY's authority undermine its original purpose, which stemmed from the proliferation of legal mafia and the judiciary's failure in internal supervision. Overlapping regulations, such as Article 32A paragraph (1) of Law No. 3 of 2009, which still grants oversight authority to the MA, often lead to conflicts between the two institutions. The presence of the KY as a crucial check and balances mechanism is essential to address misconduct caused by low judicial moral integrity, controversial rulings, limited public reporting avenues, and the esprit de corps culture. Therefore, the KY functions as an external oversight body to strengthen law enforcement, ensure judges adhere to ethical codes, and guarantee justice for the community.